2018
DOI: 10.1108/jpbm-07-2016-1282
|View full text |Cite
|
Sign up to set email alerts
|

An eye tracking study of minimally branded products: hedonism and branding as predictors of purchase intentions

Abstract: Purpose This study aims to test the relationship between consumers’ perceptions of product type (utilitarian vs hedonic) and the attentional processes that underlie decision-making among minimally branded products. Design/methodology/approach This study uses eye-tracking measures (i.e. total fixation duration) and data collected through an online survey. Findings The study shows that consumers spend more time looking at hedonic (vs utilitarian) and branded (vs unbranded) products, which influences percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 52 publications
1
37
0
2
Order By: Relevance
“…Predictive values are linked to cues associated with benefits, whereas confidence values are related to the accuracy of the judgment based on the available cues. The CUP points to intrinsic and extrinsic judgment cues about a product, and since intrinsic cues are not easily accessible, consumers often rely on product packaging as an extrinsic cue in the purchasing environment …”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictive values are linked to cues associated with benefits, whereas confidence values are related to the accuracy of the judgment based on the available cues. The CUP points to intrinsic and extrinsic judgment cues about a product, and since intrinsic cues are not easily accessible, consumers often rely on product packaging as an extrinsic cue in the purchasing environment …”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, Simmonds and Spence reported that certain visual PDEs on food products may have greater potential to attract consumers to a product than verbal PDEs. Moreover, Mundel et al determined that consumers are drawn to products through verbal PDEs such as the brand. It is possible that certain emotional and self‐concept cues are more associated with the brand image and its quality.…”
Section: Interactions Between Various Pdesmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research has highlighted the importance of hedonic and symbolic values by acknowledging the multiple channels used by consumers to experience products and services (Hirschman and Holbrook, 1982;Wilhelms et al, 2017;Fabbrizzi et al, 2018). Many scholars have started to recognize the importance of hedonic consumption by showing the significance of active motives and hedonic aspects in consumption behavior (Alba and Williams, 2013;Mundel et al, 2018). The purchase and use of material products like cars, for example, are mostly driven by symbolic value and by the pleasure derived from their usage (Mann and Abraham, 2006;Steg et al, 2001).…”
Section: The Means-end Approachmentioning
confidence: 99%
“…Although it may seem a secondary element, it is not. However, one often chooses their purchase decision based on what experts call Brand naming 6 . On the contrary what is the same, the tendency to use the brand name in purchasing decisions.…”
Section: A Force Of Packagingmentioning
confidence: 99%